A note on the age at sexual maturity of humpback whales - Best, Peter B. (J. Cetacean Res. Manage., 2020)
The conclusion of researchers in the 1950s that humpback whales reached sexual maturity at about age five was largely influenced by their interpretation of baleen tracings, and to achieve consistency with these tracings the accumulation rate of ear plug laminations (growth layer groups: GLGs) was assumed to be two per year. However, ovulation and natural mortality rates calculated by these researchers under the same assumption produced estimates that are difficult to reconcile with other biological data or with more recent estimates using individual re-sighting data. Such disparities are reduced or disappear when an annual accumulation rate is used, in which case their ear plug data would have indicated a mean age at sexual maturity of 9–11 years. Recent estimates of the age of female humpback whales at first calving using longitudinal studies of photoidentified individuals have produced conflicting results, some (from southeastern Alaska) being compatible with the earlier age-determination studies, others (from the Gulf of Maine) suggesting a much younger age.